2016
DOI: 10.3389/fimmu.2016.00480
|View full text |Cite
|
Sign up to set email alerts
|

Immune Regulation by Pericytes: Modulating Innate and Adaptive Immunity

Abstract: Pericytes (PC) are mural cells that surround endothelial cells in small blood vessels. PC have traditionally been credited with structural functions, being essential for vessel maturation and stabilization. However, an accumulating body of evidence suggests that PC also display immune properties. They can respond to a series of pro-inflammatory stimuli and are able to sense different types of danger due to their expression of functional pattern-recognition receptors, contributing to the onset of innate immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 109 publications
(114 reference statements)
1
103
0
1
Order By: Relevance
“…Human lung PDGFR-␤ϩ pericytes express proinflammatory chemokines in response to stimulation by PAMPs and DAMPs in vitro. Pericytes are increasingly being recognized as cells important in immunomodulation and tissue repair (30,43). Isolated pericytes from rodent lungs, as well as human and mouse brain, kidney and placenta, elaborate a number of chemokines and cell adhesion molecules in response to stimulation by PAMPs and DAMPs (14 -16, 24, 26, 28, 33, 42).…”
Section: L996mentioning
confidence: 99%
“…Human lung PDGFR-␤ϩ pericytes express proinflammatory chemokines in response to stimulation by PAMPs and DAMPs in vitro. Pericytes are increasingly being recognized as cells important in immunomodulation and tissue repair (30,43). Isolated pericytes from rodent lungs, as well as human and mouse brain, kidney and placenta, elaborate a number of chemokines and cell adhesion molecules in response to stimulation by PAMPs and DAMPs (14 -16, 24, 26, 28, 33, 42).…”
Section: L996mentioning
confidence: 99%
“…Ebert and C.M.B. Rouget [73] and were named by K.W. Zimmermann describing their contractile nature in 1923 [74].…”
Section: In Vivo Function Of Pericyte-mscmentioning
confidence: 99%
“…In tumor tissue, pericytes highly express αSMA, although it is often absent in quiescent pericytes in non-tumoral tissue. Recent experimental studies revealed that pericytes can actively modulate the magnitude of immune responses and may prevent lymphocyte extravasation and activation in tumor tissue [9].…”
Section: Angiogenic Vascular Cellsmentioning
confidence: 99%